2014
DOI: 10.1016/j.mad.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of: A parallel randomized trial on the effect of a healthful diet on inflammageing and its consequences in European elderly people: Design of the NU-AGE dietary intervention study

Abstract: The NU-AGE study is the first dietary intervention investigating the effect of a healthful diet providing targeted nutritional recommendations for optimal health and quality of life in apparently healthy European elderly. Results of this intervention will provide evidence on the effect of a healthful diet on the prevention of age related decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 51 publications
0
57
0
Order By: Relevance
“…In this study, we observed the effects of a 1-year Mediterranean-like diet, newly designed according to the nutritional needs of people over 65 years of age (Berendsen et al 2014), on epigenetic AA measures. We analyzed blood methylation data, obtained in a population of subjects enrolled in a multicenter trial, and we demonstrated that the nutritional intervention delivered in the NU-AGE study can slow down the epigenetic aging rate of blood in specific groups of participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we observed the effects of a 1-year Mediterranean-like diet, newly designed according to the nutritional needs of people over 65 years of age (Berendsen et al 2014), on epigenetic AA measures. We analyzed blood methylation data, obtained in a population of subjects enrolled in a multicenter trial, and we demonstrated that the nutritional intervention delivered in the NU-AGE study can slow down the epigenetic aging rate of blood in specific groups of participants.…”
Section: Discussionmentioning
confidence: 99%
“…NU-AGE was a 1-year, multicenter, randomized, singleblind, controlled trial (registered with clinicaltrials.gov, NCT01754012) with two parallel groups (i.e., dietary intervention and control) carried out during April 2012-January 2015 in five European centers in Italy, Poland, France, the Netherlands, and the UK. The recruitment of participants has been described in detail previously (Berendsen et al 2014;Santoro et al 2014). Briefly, 1279 participants aged 65-79 years, free of major overt chronic diseases for at least 2 years (i.e., cancer, severe organ disease), living independently, and free of dementia, were recruited to participate in the baseline assessment.…”
Section: Nu-age Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The present study included older men and women (n = 981; age 65-79 years) recruited within the frame of the NU-AGE project, a multi-centre study exploring determinants of healthy aging across five European countries. At screening, subjects fulfilling frailty criteria were excluded [30]. A detailed description of the recruitment process and study design has been described elsewhere [30,31].…”
Section: Subjectsmentioning
confidence: 99%
“…At screening, subjects fulfilling frailty criteria were excluded [30]. A detailed description of the recruitment process and study design has been described elsewhere [30,31]. In the context of the present study, data from France were not included due to a lack of information on accelerometer-based PA. Local ethical approval was provided by the Independent Ethics Committee of the Sant'Orsola-Malpighi Hospital Bologna (Italy-103/2011/U/Sper), the National Research Ethics Committee-East of England (United Kingdom-12/EE/0109), the Wageningen University Medical Ethics Committee (Netherlands-11/41 NU-AGE) and the Bioethics Committee of the Polish National Food and Nutrition Institute (Poland).…”
Section: Subjectsmentioning
confidence: 99%